Endoscopic Ultrasound for the Evaluation of Cystic Lesions of the Pancreas - Al-Haddad, Mohammad; El Hajj, Ihab I; Eloubeidi, Mohamad A (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Gross surgical resection specimen (distal pancreatectomy with splenectomy).